Dwelling or duelling in possibilities: how (Ir)relevant are African feminisms? - Muhammad Alkali,; Rosli Talif,; Wan Roselezam Wan Yahya,; Jariah Mohd Jan, (Penerbit UKM, 2013)
In its four decades of rebirth, the world has debated (enough) the relevance of feminism, but there is, surprisingly, refreshingly emergent dimensions at the turn of the twenty-first century: feminisms from feminism flowing from Africa. The theories or models of Womanism, Stiwanism, Motherism, and Nego-feminism, with their underlying assumptions and values,were all born at various end times of the twentieth century with a common objective of seeking gender justice. This paper examines the crucial question of how relevant these models are to the global practice of woman as human. What propels their separateness, and why didn‘t they combine to make a more solid stance on the plight of the African woman? In fact, why can‘t they simply identify with the general feminism? Put differently, are they dwelling in the same terrain or are they separable and easily recognisable discourses duelling in possibilities for the woman in Africa in particular and the woman of the globe in general? More specifically, how (ir)relevant are African feminisms?In trying to answer these questions, the paper presents a critical review of the afore-mentioned theories of African feminisms with the goal of providing readers an understanding of what is new in each model, and what is similar or different between the various strands of African feminisms. The paper concludes with the author‘s analysis of the model that holds the best promise or possibilities for African feminism to achieve its seemingly elusive goal of gender equality.